Assessment of slot sizes in self-ligating brackets using electron microscopy - Bhalla Nidhi B.; Good Sarah A.; McDonald Fraser; Sherriff Martyn; Cash Alex C. (Sciendo, 2023)
To measure the slot dimensions of 0.022 inch self-ligating upper central incisor brackets from six manufacturers using electron microscopy, to compare the measured dimensions with the manufacturers' published dimensions, and to determine if the walls of the slots were parallel.